Suggestion of new terminology and classification of the hand techniques by angular momentum in the taekwondo poomsae - Yoo, S.-H.; Jung, K.-H.; Ryu, J.-S. (Korean Journal of Sport Biomechanics, 2016)
Objective: The purpose of this study is to suggest new terminology for the ninety-five hand techniques based on the significance of their angular momentum, determined by analyzing each technique's influence or impact on the compartmentalized angular momentum of the trunk, upper arm, and forearm in the Taekwondo Poomsae. Method: An athlete who won the 2014 World Taekwondo Poomsae championship was selected and agreed to participate in the data collection phase of our investigation. The video data was collected using eight infrared cameras (Oqus 300, Qualysis, Sweden) and the Qualisys Track Manager software (Qualisys, Sweden). The angular momentum of each movement was then calculated using the Matlab R2009a software (The Mathworks, Inc., USA). Results: The classification of the ninety-five hand techniques in the Taekwondo Poomsae based on the significance of each segment's momentum is as follows. Makgi (blocking) is classified into fourteen categories, jireugi (punching) is classified into three categories, chigi (hitting) was classified into six categories, palgupchigi (elbow hitting) was classified into four categories, and jjireugi (thrusting) was classified two categories. Conclusion: This study offers a new approach, based on a biomechanical method, to the classification of the hand techniques that reflect kinesthetic motions in the Taekwondo Poomsae.